Engineered Bacillus pumilus laccase-like multi-copper oxidase for enhanced oxidation of the lignin model compound guaiacol. Issue 6 (8th May 2017) - Ihssen, Julian; Jankowska, Dagmara; Ramsauer, Thomas; Reiss, Renate; Luchsinger, Ronny; Wiesli, Luzia; Schubert, Mark; Thöny-Meyer, Linda; Faccio, Greta
Abstract: Laccases and laccase-like multi-copper oxidases (LMCOs) are versatile and robust biocatalysts applied in a variety of oxidative processes, and various studies have attempted to improve their catalytic activity. Here we report the engineering of a bacterial LMCO for enhanced oxidation of the lignin-related compound guaiacol by a combination of structure-guided mutagenesis and DNA shuffling. Mutant L9 showed a 1.39 mM K m for guaiacol and a 2.5-fold increase in turnover rate ( k cat / K m = 2.85·10 4 M −1 s −1 ).